New treatment options in elderly patients with Diffuse Large B-cell Lymphoma - Arcari, Annalisa; Cavallo, Federica; Puccini, Benedetta; Vallisa, Daniele (Frontiers in Oncology, 2023)
Most patients with Diffuse Large B-cell Lymphoma (DLBCL) are old (>65 years of age) and this population is expected to increase in the following years. A simplified geriatric assessment based on a careful evaluation of the fitness status and comorbidities is essential to choose the correct intensity of treatment. Fit older patients can benefit from a standard immunochemotherapy, while unfit/frail patients frequently need reduced doses or substitution of particular agents with less toxic ones. This review focuses on new therapies (e.g., polatuzumab vedotin, tafasitamab, bispecific antibodies) that have indicated promising results in relapsed/refractory patients, particularly in cases not eligible to transplant. Some of these new drugs have been tested as single agents or in combinations as first-line treatment, aiming to improve the outcome of the traditional chemotherapy. If preliminary efficacy and safety data are confirmed in future clinical trials, a chemo-free immunotherapic approach could become an alternative option to offer a curative treatment even in frail patients.